Relação lance livre/colocação NBB temporada 2014/2015 e os pontos fortes das equipes - Fulaneto, Newton de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
James Naismith, a Professor of Physical Education of the Young Men's Christian Association in the year 1891, in the United States, created basketball. Augusto Shaw was responsible for bringing the sport to Brazil, when he has invited to teach at the traditional Mackenzie College in Sao Paulo in 1894. The free throw was not written in the original 13 rules of the game, and was only introduced in 1895, which according to the current rules, consists of the opportunity of extra shooting, provided due to a foul committed by the opponent in the shooting or overcoming the limit of five fouls committed in the fourth. Each successful free throw is one more point, and the amount of free throws is according to the possible score in the act shooting (2 or 3 point line), or two free throws after a foul out of the shooting act, when exceeded the limit established without suffering such punishment. In case of points and foul, the player must shoot a free throw. The free throw must be shooting by the player who suffered the foul behind the foul line, at a distance of 4.6 meters from the table. In the first round of NBB 2014/2015, two of the seven games, or almost 30%, could have had a different result if the free throws were better shoot. In the match between Rio Claro and Palmeiras, if the team of Rio Claro successful the three free throws that failed, the game would have gone to the overtime. Already in the match between BAURU X BRASILIA, the team of Bauru would win the match if successful four of the five free throws wrong. Because of these facts, the study will verify a possible relationship between the rank of the teams in the NBB season 2014/2015, and the percentage of the free throw, analyzing whether the ranked teams in the league are the same with best free throws. If is no relationship, it will be a survey of which factors were decisive for these teams to compensate for this inefficiency and stand out over other teams...

O basquetebol foi criado no ano de 1891, nos Estados Unidos. Seu criador foi o professor de Educação Física, James Naismith, da Associação Cristã de Moços. Augusto Shaw foi o responsável por trazer o esporte para o Brasil após receber o convite em 1894 para lecionar no tradicional Mackenzie College, em São Paulo. O lance livre não esteve presente nas 13 regras originais do jogo, e só foi introduzido em 1895, na qual, segundo as regras atuais, consiste na oportunidade de arremesso (s) extra (s), proporcionado devido uma falta cometida pelo adversário no ato do arremesso ou ao ultrapassar o limite de cinco faltas cometidas no quarto. Cada lance livre acertado contabiliza um ponto, e a quantidade de lances livres arremessados é de acordo com a possível pontuação no ato do arremesso (linha de 2 ou 3 pontos), ou em dois lances livres após uma falta fora do ato do arremesso, quando ultrapassado o limite estabelecido sem sofrer tal punição. No caso de cesta e falta, premia-se a chance de um ponto extra. O lance livre deve ser arremessado obrigatoriamente pelo jogador que sofreu a falta atrás de uma linha (foul line), a uma distância de 4,6 metros da tabela. Na primeira rodada da NBB 2014/2015, dois dos sete jogos, ou seja, quase 30%, poderiam ter tido um resultado diferente, se os lances livres fossem melhor aproveitados. Na partida entre Rio Claro e Palmeiras, se a equipe de Rio Claro convertesse os 3 lances livres que falharam, o jogo teria ido para a prorrogação. Já na partida entre BAURU X BRASILIA, a equipe de Bauru, ganharia a partida se convertesse 4 dos 5 lances livres errado. Diante de tais fatos apresentados, esse estudo irá verificar uma possível relação entre a colocação da equipe na LNB (NBB) temporada 2014/2015, e o porcentual de aproveitamento no lance livre, ou seja, será analisado se os times melhores colocados no campeonato, são os mesmos que melhor usufruem os lances livres...
Keywords: Basquetebol; Basquetebol - Regras; Equipes de basquetebol - 2014-2015